Diarrhea in pediatric recipients of solid organ or bone marrow transplants. Issue 43 (29th October 2021) - Phrommas, Jirachart; Tanpowpong, Pornthep; Getsuwan, Songpon; Lertudomphonwanit, Chatmanee; Chantarogh, Songkiat; Anurathapan, Usanarat; Treepongkaruna, Suporn
Abstract : Abstract: Diarrhea is common in adults after solid organ transplantation (SOT) and bone marrow transplantation (BMT), but data in children are limited. Therefore, we aimed to determine the incidence and etiology of pediatric early-onset diarrhea in post SOT and BMT. We reviewed children aged 6 months to 18 years who underwent liver transplantation, kidney transplantation or BMT between January 2015 and December 2019 with duration of diarrhea > 72 hours within the first 6 months after transplantation. Clinical data and diarrheal course were collected. Regression analyses were performed to define factors associated with the interested outcomes. Among 252 transplanted patients, 168 patients (66.6%) had 289 documented episodes of diarrhea. A diagnosis of 68.2% of post-transplant diarrhea remained 'indefinite'. Enteric infection in SOT and gastrointestinal acute graft-versus-host disease (GI-aGVHD) in BMT were the commonly identified etiologies. Among 182 episodes among BMT children, skin rash was more pronounced when compared the ones with diarrhea > 7 days vs ⩽ 7 days (odds ratio [OR] 13.9; 95% CI 1.8, 107.6). Males were more likely to develop GI-aGVHD as compared to females (OR 8.9). We found that GI-aGVHD was more common in the ones with skin rash and the presence of white blood cells in stool examination (OR 8.4 and 3.1, respectively). Deaths occurred in 7.7%. Two-thirds of post-transplant children experienced at least one episode of early-onset diarrhea, of which the etiology mainly remains undefined. Various clinical factors of prolonged/chronic diarrhea and GI-aGVHD may help clinicians when managing these children.